2005
DOI: 10.1007/s11060-005-2318-1
|View full text |Cite
|
Sign up to set email alerts
|

CD117 expression in glial tumors

Abstract: C-kit is a proto-oncogene involved in normal growth and development and neoplastic processes, and its product, CD117, is a highly specific immunohistochemical diagnostic marker for gastrointestinal stromal tumors (GISTs). Because GISTs that express immunohistochemically-detectable CD117 respond dramatically to treatment with tyrosine kinase inhibitors, identification of central nervous system tumors that express CD117 might open new therapeutic approaches for treatment of brain tumors. Specimens from 52 glial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
3
18
1
Order By: Relevance
“…b Low-grade astrocytoma shows staining of some cytoplasm (white arrowheads) and most processes (black arrowheads) (original magnification: 400×). Reprinted with permission from Springer+Business Media ©2005 [14] Recently, a combined analysis of two phase II studies of 231 unselected patients with recurrent GBM treated with imatinib and hydroxyurea confirmed the previously reported limited benefit of this combination [9]. In this analysis, a modest response rate of 3.4% and poor 6-month PFS of 10.6% were seen [9].…”
Section: Combination Therapy With Imatinib For Malignant Gliomasupporting
confidence: 65%
See 1 more Smart Citation
“…b Low-grade astrocytoma shows staining of some cytoplasm (white arrowheads) and most processes (black arrowheads) (original magnification: 400×). Reprinted with permission from Springer+Business Media ©2005 [14] Recently, a combined analysis of two phase II studies of 231 unselected patients with recurrent GBM treated with imatinib and hydroxyurea confirmed the previously reported limited benefit of this combination [9]. In this analysis, a modest response rate of 3.4% and poor 6-month PFS of 10.6% were seen [9].…”
Section: Combination Therapy With Imatinib For Malignant Gliomasupporting
confidence: 65%
“…Cellular expression of CD117, as detected by immunohistochemistry (IHC), has been reported in up to 75% of gliomas in one series ( Fig. 1) [14]. However, this may be an overestimate, as in one large series of more than 3,000 tumors of varying histology, c-KIT protein expression by IHC was found in only 4 of 73 gliomas [13].…”
Section: C-kit In Malignant Gliomamentioning
confidence: 96%
“…Cetin et al 10 studied a series of 52 glial tumors and found that 75% were positive for KIT, and the proportion of high-grade tumors was significantly greater than of low-grade tumors.…”
Section: Figure 1 -Correlation Between Microvessel Density (Mvd) and mentioning
confidence: 99%
“…The proto-oncogene KIT encodes CD117, a transmembrane tyrosine kinase that has a well-established role in several human tumors; cellular expression of CD117 has already been detected by immunohistochemistry in gliomas 10 . In addition to protein expression, it has also been suggested that KIT gene amplification may be observed more commonly in glioblastomas and astrocytic tumors than in oligodendrogliomas, which constitute gliomas outside the astrocytic lineage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…2). Although glioblastoma cells express a variety of self-antigens including receptor protein tyrosine phosphatase-b, receptor tyrosine kinase EphA2, CD117, GLEA1, GLEA2, and PHD-finger protein-3 (PHF-3), YKL-40, cyclooxygenase-2, Her2/neu, gp100, AIM-2, MAGE-1 [22,[43][44][45][46][47][48], they seldom induce effective anti-tumor immune responses. This observation is probably related to the fact that glioblastoma cells do not express HLA-DM, GILT, and essential co-stimulatory molecules (e.g., CD80, CD86), and optimal levels of class II molecules.…”
Section: Implications Of Atra and Ifn-c In Devising Whole-cell Vaccinmentioning
confidence: 99%